Peran Perawat dalam Pencegahan Infeksi pada Pasien Post Operasi Appendiksitis di Ruang Teratai RSUD Undata Palu - Andy Nurhany (Biocelebes, 2008)
There are two functions of hhe nurse in society, consist of a healthy worker and a healthy educator. As a healthy worker, they doing direct or indirect nurse to client as an individu, family and society. They are being as comforter, protector, advocate, communicator and rehabilitator. In the other hand, nurse as a health educator giving the healthy education training to individu, family and society. This aim research was observed how many percent of the nurse was doing an infection preventive on Appendictis Post Operation patiens in the Teratai Block of RSUD Undata Palu. The result showed that 56,52% of the nurse have doing their function as a good healthy worker, and the other 43,48% are not. Meanwhile, 78,3% have doing their function as a healthy educator and 21,7% are not. Commonly, it can conclusion that the nurse in Teratai Block of RSUD Undata Palu was doing their function as a healthy worker and a healthy educator. Key words: Nurse, Appendictis, Infection preventive